Implementation of Distraction Therapy Through Nature Videos in Pre-Caesarean Section (CS) Patients with Anxiety Nursing Problems in the Khadijah Inpatient Ward, ANNISA Women's and Children's Hospital - Almaderi Putra; Angga Arfina; Rina Herniyanti; Ulfa Hasanah (PT. Edukasi Ahmad Kirang, 2026)
Background: Delivery through Sectio Caesarea (SC) often causes anxiety in preoperative mothers due to lack of information, concerns about fetal safety, and fear of the surgical procedure. Anxiety can trigger physiological responses such as increased heart rate, sleep disturbances, and emotional tension that may affect the mother’s condition before delivery. Therefore, effective non-pharmacological interventions are needed to help reduce patient anxiety. One intervention that can be used is distraction therapy through nature videos, which provide calming visual stimuli and help divert the patient’s attention. This study aimed to determine the effectiveness of distraction therapy using nature videos in reducing anxiety levels among pre-Sectio Caesarea patients in the Khadijah inpatient ward of RSIA Annisa. Methods: This study used a case study design based on Evidence-Based Practice Nursing. The research was conducted in the Khadijah inpatient ward of RSIA Annisa in December 2025 with two pre-Sectio Caesarea patients experiencing moderate anxiety. Data were collected through observation, interviews, and measurement of anxiety levels using the Hamilton Anxiety Rating Scale (HARS). The intervention consisted of distraction therapy using nature videos for 15 minutes each day for three consecutive days after the patients provided informed consent. Results: The results showed a decrease in anxiety levels in both patients. The HARS score of the first patient decreased from 26 to 13, while the second patient’s score decreased from 25 to 12. Patients also appeared calmer, showed reduced restlessness, and experienced improved rest quality after the intervention. Conclusion: Distraction therapy using nature videos is effective in reducing anxiety in pre-Sectio Caesarea patients and can be used as a non-pharmacological nursing intervention to improve patients’ psychological comfort before surgery.